2017
DOI: 10.1007/s00423-017-1648-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous versus surgical strategy for tracheostomy: a systematic review and meta-analysis of perioperative and postoperative complications

Abstract: PROSPERO CRD42015021967.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 53 publications
1
65
0
7
Order By: Relevance
“…stated that mechanical ventilation is applied to approximately 800 000 patients per year in the USA, and emphasized that the frequency of tracheostomy showed an increase in parallel to the increase in mechanical ventilation rates . As a result of the high complication rates of the traditional ST approach, such as bleeding, infection, fistula, pneumothorax and tracheal stricture (TS), new techniques were developed …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…stated that mechanical ventilation is applied to approximately 800 000 patients per year in the USA, and emphasized that the frequency of tracheostomy showed an increase in parallel to the increase in mechanical ventilation rates . As a result of the high complication rates of the traditional ST approach, such as bleeding, infection, fistula, pneumothorax and tracheal stricture (TS), new techniques were developed …”
Section: Discussionmentioning
confidence: 99%
“…10 As a result of the high complication rates of the traditional ST approach, such as bleeding, infection, fistula, pneumothorax and tracheal stricture (TS), new techniques were developed. 3,4,7 Mortality rates have generally been reported to be lower in patients who received percutaneous tracheostomy, and it has also been emphasized that the tracheostomy method is not the only criteria determining the mortality rate. 7,10,11 In the present study, we evaluated the mortality of both groups in two categories as procedure-related mortality and total mortality in ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 However, two recent systematic reviews showed no statistically significant differences with respect to postoperative bleeding rates, 29 surgical bleeding, and mortality. 29,30 The longitudinal follow-up suggested that the delayed complications, which included clinically significant tracheal stenosis, were similar compared with these techniques. 3,33 PDT has gained wide acceptance, due to its great ease, for the advantages that have been observed in several studies, so it has become the predominant method of tracheotomy placement.…”
Section: Percutaneous Dilatational and Surgical Tracheostomymentioning
confidence: 96%
“…The first is the conventional surgical tracheostomy (ST) that is the classic technique of performing a tracheostomy until the next generation or percutaneous dilatational tracheostomy (PDT) arrived. 27 Several clinical studies, meta-analysis, systematic reviews, and secondary data analysis have compared PDT and ST, suggesting equivalences and even the potential superiority of PDT over ST. [28][29][30][31][32] Two meta-analysis and one systematic review showed a statistically significant reduction in stoma infection and operative time with PDT. 28,29,31 In addition, one of the two meta-analysis showed that PT techniques reduced the chances of major postoperative bleeding.…”
Section: Percutaneous Dilatational and Surgical Tracheostomymentioning
confidence: 99%